Розробка засобів для інтенсифікації процесів теплообміну в акумуляторах теплоти на основі акумулюючих матеріалів фазового переходу - Антипов, Є. О. (Енергетика і автоматика, 2017)
Development tools for the intensification of heat transfer in heat accumulators BASED MATERIALS accumulating phase transitionI. AntypovAnnotation. The possibility of increasing heat discharge characteristics of the heat accumulators on the basis of accumulating the phase transition materials. After analyzing the dynamics of the value of temperature fields in the heat accumulator, as well as received the effective settings step of laying a heating cable in the case of the object.Key words: heat accumulator, heat-accumulating material, phase transformations, heat exchange surface